2017
DOI: 10.1002/jcph.910
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Adult Experience to Pediatrics in Oncology Drug Development

Abstract: Pediatric drug development in the United States has grown under the current regulations made permanent by the Food and Drug Administration Safety and Innovation Act of 2012. Over 1200 pediatric studies have now been submitted to the US FDA, but there is still a high rate of failure to obtain pediatric labeling for the indication pursued. Pediatric oncology represents special problems in that the disease is most often dissimilar to any cancer found in the adult population. Therefore, the development of drug dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Pediatric extrapolation of efficacy is generally not a concept that can be applied to pediatric oncology, except under special circumstances . However, the application of exposure‐matching that is frequently used in pediatric extrapolation to pediatric oncology will have to be explored, as will algorithms related to pediatric study planning and extrapolation.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric extrapolation of efficacy is generally not a concept that can be applied to pediatric oncology, except under special circumstances . However, the application of exposure‐matching that is frequently used in pediatric extrapolation to pediatric oncology will have to be explored, as will algorithms related to pediatric study planning and extrapolation.…”
Section: Discussionmentioning
confidence: 99%
“…Because pediatric oncology indications are mostly unique and dissimilar to the disease in adults (ie, disease progression is not similar to adults), full or partial extrapolation approaches based on PK and PK/PD are generally not possible and the pediatric study objectives would focus on providing evidence of effectiveness and safety and to characterize the PK and exposure‐response relationships in pediatric oncology patients to enable optimal dosing. Understanding of tumor biology and markers of disease in pediatric patients along with bridging of knowledge from trials in adult patients may offer more opportunity to inform pediatric clinical trials . Despite these challenges, an analysis of the labels of 34 cancer drugs in Table where the pediatric cancer was evaluated in adults (except for conditions that are exclusively in pediatrics only) revealed that after correcting for body size (mg/kg or mg/m 2 ), for approximately 50% of these drugs the pediatric and adult doses were the same, 13% were within 70% to 130% of the adult dose, 20% had a higher adult dose (≥50%), and 20% did not have an adult dose (due to condition existing only in pediatrics, such as neuroblastoma) for comparison (Figure ).…”
Section: Clinical Pharmacology Considerationsmentioning
confidence: 99%
“…As part of the drug development process, pediatric applications have grown since the FDA formalized the Innovation Act of 2012. Leong and colleagues provide a comprehensive account of the various methods used to bridge adult data to pediatric patients, although challenges remain because of the dissimilarity of disease, especially cancer, between these patient populations. These bridging methods include extrapolation of pediatric efficacy from adult studies, inclusion of adolescents in adult trials, and bridging of adult dosing to pediatric patients.…”
mentioning
confidence: 99%